Maternal knowledge on iron and folic acid supplementation and associated factors among pregnant women in a rural County in Kenya - Mary Wanjira Kamau; Waithira Mirie; Samuel Thuo Kimani (Elsevier, 2019)
Background: Iron and folic acid supplementation (IFAS) programme is a key global intervention for control of anaemia in pregnancy. Due to persistently high anaemia rates during pregnancy, Kenya, adopted IFAS programme in 2010 as a high impact nutrition interventions to control anaemia in pregnancy. Despite free provision of IFAS tablets, compliance has remained low over the years. Studies have associated high maternal knowledge with higher supplement use. Objective: To determine maternal IFAS knowledge and associated factors, including socio-demographic characteristics, source of IFAS information and their relationship with IFAS knowledge, among pregnant women in Kiambu County. Methods: This was a cross-sectional study involving 364 pregnant women aged 15-49 years. Using two stage sampling, one sub-County was selected and five public health facilities. A pre-tested structured questionnaire consisting of socio-demographic data, source of IFAS information and maternal IFAS knowledge was used. Descriptive and inferential statistics were computed using STATA. Results: Of 364 respondents interviewed, although 67.3% had heard of IFAS, 40.9% (149) scored highly on IFAS knowledge. Despite health care providers (63%) being most reported source of information, highest level of knowledge was among women who obtained information from brochures (91%) and community health workers (CHWs) (87%). Women aged ≥30 years, married, multiparous and earning ≥USD 100 were most likely (p ≤ 0.05) to score high. Conclusions: Maternal IFAS knowledge was fair and was associated with maternal age, marital status, parity, employment, monthly income, availability of brochures and support from CHWs. Strengthening provision of IFAS learning materials and enhancing CHWs involvement is recommended. Keywords: Iron and folic acid supplementation (IFAS), Maternal knowledge, Pregnant women, Information source, Anaemia control, Nutrition